Characteristics of Patience in Parents with Autistic Children: A Phenomenological Study - Ahmad Hidayat; Muhammad Azhar; Muhammad Anis; Halim Purnomo; Rahmad Muliadi (Universitas Muhammadiyah Yogyakarta, 2023)
The effectiveness of early intervention involving parents determines the success of services for children with autism. The study aims to deepen our understanding of how Muslim parents developed patience in educating, training, and teaching their autistic children. This study used phenomenology to explore the characteristics of patience in Muslim parents with autistic children in a low-income class. Respondents were four mothers who were actively caring for their children and registered with the Autism Service Center, a local autism service center in Riau Province. The findings showed the types of characteristics associated with patience. Parents with moderately autistic children are patient with self-control patterns. At the same time, the characteristics of patience in parents with severely autistic children are patience with patterns of grit, resilience, and hardiness. The overall characteristics of patience cannot be separated from the characteristics of voluntary patience, which come from the belief in Allah. The characteristics of patience contain an active patient characteristic.